Campus Recreation and Fitness Center Utilization During the COVID-19 Pandemic - Keagan Kiely; William A. Mase; Bridget Melton; Haresh Rochani (Georgia Southern University, 2021)
Background The impact of the COVID-19 pandemic has far reaching effects for college students' health and physical activity behaviors. This analysis focuses on university student fitness center usage pre and during the COVID-19 pandemic. Researchers hypothesized a reduction in fitness center utilization when comparing Fall 2019 to Fall 2020 utilization rates. Methods Patterns of the recreation center and fitness center utilization during the COVID-19 pandemic are compared to pre-pandemic patterns of a matched time period in the previous academic year in an observational study. Overall utilization was evaluated using secondary data from the university's recreation center data system. Six weeks of utilization data were pulled for investigation across the two years of interest. Time periods evaluated included Fall semester 2019 (August 19, 2019 - September 29, 2019) and Fall semester 2020 (August 17, 2020 - September 27, 2020). Poisson regression analysis was used where statistical significance levels were set to 0.05. Results There was a statistically significant reduction in recreation center participation from 2019 to 2020 (Mean±SD: 1683.1 ± 888.6 to 726.4 ±339.9). Furthermore, student participation decreased in all areas of the fitness center usage from 2019 to 2020 (cardio deck, machine weights, and free weights Mean±SD: 12.5±8.9 to 5.4±4.2, 17.6±9.5 to 8.9±5.4, 27.7±13.1 to 17.9±8.4). While the overall participation decreased, the proportion of utilization increased in the free weights area (B = 0.2446; 95% CI 0.1604 - 0.3289; p Conclusions This study is one of the first to evaluate the effect the COVID-19 pandemic has on participation in a university recreation center. This study will help generate questions and guide future research analyzing trends of physical activity during the COVID-19 pandemic.